2008
DOI: 10.1093/intimm/dxn007
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4{middle dot}Ig converts naive CD4+CD25- T cells into CD4+CD25+ regulatory T cells

Abstract: CTLA-4 x Ig was originally designed as an immunosuppressive agent capable of interfering with the co-stimulation of T cells. In the present study, we demonstrate that CTLA-4 x Ig, in combination with TCR ligation, has the additional capacity to convert naive CD4+CD25- T cells into Foxp3+ regulatory T (T(reg)) cells, as well as to expand their numbers. The CD4+CD25+Foxp3+ T(reg) generated by CTLA-4 x Ig treatment in vitro potently suppress effector T cells. Extending this in vivo, we show that systemic administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 48 publications
1
36
2
Order By: Relevance
“…Furthermore, some experimental evidence suggested that the tolerogenic efficacy of costimulation blockade by CTLA4-Ig even critically depended on Foxp3 + T reg cells (40,41). The sources of T reg cells promoted by costimulation blockade included adaptive T reg cells (42), conversion of CD4 + CD25 + Foxp3 j cells to CD4 + CD25 + Foxp3 + cells (43), or as in the present study, thymus-derived T reg cells (24).…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, some experimental evidence suggested that the tolerogenic efficacy of costimulation blockade by CTLA4-Ig even critically depended on Foxp3 + T reg cells (40,41). The sources of T reg cells promoted by costimulation blockade included adaptive T reg cells (42), conversion of CD4 + CD25 + Foxp3 j cells to CD4 + CD25 + Foxp3 + cells (43), or as in the present study, thymus-derived T reg cells (24).…”
Section: Discussionsupporting
confidence: 67%
“…While one report suggests that abatacept therapy inhibits activation-induced cell death of Treg cells, which resulted in their increased proportion in the blood (24), others suggest that abatacept therapy diminishes the frequency of Treg cells in RA patients (25). Murine studies have also been equivocal, with systemic administration of CTLA-4Ig being reported as leading to an increase in CD41CD251 Treg cells (45). However, none of these studies could distinguish between natural or inducible Treg cells, as they used polyclonal T cell populations or peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive data in mice have demonstrated that antigen-specific iTreg can be induced from previously nonregulatory CD4 ϩ CD25 Ϫ cells. [10][11][12][13] In humans, despite that a regulatory phenotype could be induced from CD4 ϩ CD25 Ϫ T cells, 14 there are few functional studies showing acquisition of suppressive activity by stimulated CD4 ϩ CD25 Ϫ T cells in healthy subjects. [15][16][17] Whether autoantigen-specific Treg could be converted from CD4 ϩ CD25 Ϫ T cells in patients with autoimmune diseases has not been reported.…”
Section: Introductionmentioning
confidence: 99%